Complexes of hydrogen peroxide and DNA phosphate group in quantum chemical calculations - Piatnytskyi, D. V.; Volkov, S. N. (Biophysical Bulletin, 2018)
Background: Molecules of hydrogen peroxide (H2O2) can be formed during radiolysis process in water medium after irradiation. A hypothesis about the possible role of hydrogen peroxide in blocking of processes of nonspecific DNA recognition by proteins is proposed in [1]. As one of the most long-living products, H2O2 molecules can diffuse considerable distances in the intracellular medium and reach DNA in the cell nucleus and form complexes with macromolecule phosphate groups. To confirm this hypothesis, the quantum chemical calculations of complexes structure of hydrogen peroxide molecule with atomic groups of the DNA backbone are performed.Objectives: To determine the optimal geometries and formation energies of stable complexes of hydrogen peroxide with DNA phosphate group. To perform a comparative analysis of hydrogen peroxide and water molecules binding to phosphate group based on quantum chemical calculations.Materials and Methods: The complexes which consist of phosphate group, hydrogen peroxide, water molecules, and sodium counterion are analyzed. The optimization of complex geometry and energy calculations is performed using the methods of quantum chemistry within Gaussian 03 software: HF/6-31+G(d,p), MP2/6-31+G(d,p), B3LYP/6-31+G(d,p).Results: This research shows that the hydrogen peroxide molecule as well as water molecule can form stable complexes with phosphate group, especially with the presence of sodium counterion Na+. The results of complex formation calculations with atom-atom potential functions method are confirmed. It is shown that the presence of sodium counterion significantly influences the geometry of the hydrogen peroxide complex with the phosphate group. The performed calculations indicate the possibility of hydrogen peroxide geometry change in the processes of complex formation.Conclusions: The obtained results confirm the possibility of stable complexes forming for hydrogen peroxide and phosphate group. Prolonged situation of H2O2 molecule near the DNA backbone may block the nucleic-protein recognition processes as well as damage the macromolecule via decay into OH-radicals in close proximity to double helix.